A study of soil erosion rates using 239Pu, in the wet-dry tropics of northern Australia. (January 2020) - Lal, R.; Fifield, L.K.; Tims, S.G.; Wasson, R.J.; Howe, D.
Abstract: The Daly River drains a large (52500 km 2 ) and mainly undisturbed catchment in the Australian wet–dry tropics. The basin landscapes are mantled by a thick veneer of kandosol soil which has developed under varying rates of erosion, uplift, bedrock type and climate and has been identified as being suitable for agriculture. Commencement of large scale clearing and cropping since 2002 have raised concerns about the increased loss of top soil from the land clearing and cultivation activities adjacent to the Daly River. This study was undertaken to determine the modern soil loss rates which can be used to develop a sustainable soil conservation strategy for this catchment. 239 Pu, released in the 1950s and 1960s by atmospheric nuclear weapons tests, is used to obtain a quantitative assessment of recent rates of soil loss. Soil cores 30–40 cm deep have been collected from fields with various land uses including peanut and hay cropping and cattle grazing. Cores taken from undisturbed and unburnt areas in open eucalypt woodland have been used as reference sites. The soil loss rates have been established by comparing the excess or deficiency of the 239 Pu tracer over that of the reference sites. Since land use practices in the catchment are similar, it is likely that the measured soil loss rates are indicative of soil loss rates over the Daly Basin as well. The development of 239 Pu as a soil tracer represents a viable alternative to the traditionally used 137 Cs tracer. This also represents a new tool in the quantification of catchment soil loss and the adoption of appropriate soil conservation strategies for the tropical regions and regions where increasing settlement and agriculture are encroaching on catchment slopes. Highlights: In this study modern soil loss rates were determined using 239 Pu. 239 Pu was released in the 1950s and 1960s by atmospheric nuclear weapons tests. The development of 239 Pu as a soil tracer represents a viable alternative to the traditionally used 137 Cs tracer. This represents a new tool in the quantification of catchment soil loss for the Australian semi arid tropical region.